KEBIJAKAN PENDIDIKAN AGAMA ISLAM DARI MASA KE MASA DI INDONESIA DALAM PERSPEKTIF DYNAMIC GOVERNANCE - Erni Qomariyah; Ahmad Sultra Rustam (Journal Publicuho, 2024)
This article explores the evolution of Islamic Religious Education (IRE) policy in Indonesia over time through the lens of 'Dynamic Governance'. Utilizing policy implementation theory approaches, this study analyzes how changes in IRE policy have impacted the educational experiences of students and the community at large. By examining various historical periods and their influence on educational policy, this research presents in-depth insights into how IRE has adapted to the changing demands and expectations of society and government. Focused on the restructuring and modernization of the Islamic education system, this article aims to elucidate the importance of policy adaptation to reflect Islamic values relevant to contemporary developments as well as the challenges and constraints encountered in its implementation. The primary goal of this writing is to offer a new perspective on the implementation of religious education policy that can support efforts to enhance the quality of Indonesian human resources in the context of social diversity and current dynamic needs.